2017
DOI: 10.1021/acs.energyfuels.7b01301
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide over Silica-Doped Alumina Catalyst for Catalytic Steam Reforming of Toluene as a Surrogate Tar Biomass Species

Abstract: An iron oxide over silica-doped alumina catalyst was successfully synthesized using one-pot, solvent-deficient method. The prepared Fe 2 O 3 /SiO 2 −Al 2 O 3 catalyst was characterized using TGA/DTG, XRD, N 2 adsorption isotherm, NH 3 -TPD, and SEM. The TGA/DTG and XRD results show that the presence of Si enhances the stability of γ-Al 2 O 3 support at high temperatures. The prepared Fe 2 O 3 /SiO 2 −Al 2 O 3 catalyst was obtained by calcination at 950 °C, with a high BET specific surface area (49 m 2 /g). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 61 publications
4
29
0
Order By: Relevance
“…Reactant converted to (phenyl boronic acid trimer)-GC-MS [conversion 100%] Reaction conditions: 1 (0.3 mmol), 2 (0.9 mmol) and catalyst (8wt%Fe/SBA-15) (100mg) in DCE ( 2 respectively were shown in Table S1. The first desorption peak at 271°C has been ascribed previously to under coordinated weak Lewis acidic Si-Fe-OH, and it has been suggestively attenuating upon SBA-15 deposition [24]. The second desorption peaks at 476°C has been assign moderated acid site its belong to coordinate the Fe-O-Si of in the mesopore region of .…”
mentioning
confidence: 88%
“…Reactant converted to (phenyl boronic acid trimer)-GC-MS [conversion 100%] Reaction conditions: 1 (0.3 mmol), 2 (0.9 mmol) and catalyst (8wt%Fe/SBA-15) (100mg) in DCE ( 2 respectively were shown in Table S1. The first desorption peak at 271°C has been ascribed previously to under coordinated weak Lewis acidic Si-Fe-OH, and it has been suggestively attenuating upon SBA-15 deposition [24]. The second desorption peaks at 476°C has been assign moderated acid site its belong to coordinate the Fe-O-Si of in the mesopore region of .…”
mentioning
confidence: 88%
“…With pelletized catalysts, where much more acidic sites (Al2O3, montmorillonite) are present in the support material, there are more possibilities for the adsorption of H2O and CO2 or even naphthalene. Adnan et al [46] observed in their investigation of toluene conversion with Fe2O3/SiO2-doped Al2O3 that the strong acidic sites promote conversion reactivity, which is controlled by the equilibrium between the strong acidic sites and the surface of the catalyst. In the case of steam We assume that in the first step of the mechanism of naphthalene conversion, which takes place at low temperatures, naphthalene is adsorbed on metal cations via π-electrons either from one or both aromatic rings.…”
Section: Mechanism Of Naphthalene Conversion and Role Of The Support Materialsmentioning
confidence: 99%
“…However the main challenge of gasification is to avoid tar (a mixture of complex compounds) formation in the gasified products because this causes fouling in the pipes, filters, turbines, or gas engines , . As such, tar formation reduces the overall efficiency of gasification of the microalgae biomass.…”
Section: Biofuel Production Processesmentioning
confidence: 99%